Tympanoplasty type 1 in the treatment of patients with sclerotic mastoid: anatomical and functional results - Dündar, Rıza; Kemal Soy, Fatih; Kulduk, Erkan; Özbay, Can; Özkul, Yılmaz; Yükkaldıran, Ahmet (ENT Updates, 2014)
Objective: To evaluate success of tympanoplasty type 1 in the treatment of patients with sclerotic mastoid bone. Methods: A retrospective study where 92 patients with non-cholesteatomatous chronic suppurative otitis media were recruited during the period of 2010 to 2012. Patients were managed medically and after dryness of their perforations they were operated upon. Ninety-two patients underwent type 1 tympanoplasty alone without cortical mastoidectomy. Underlay technique with chondroperichondrial graft was performed for all patients. Results: Mean air-bone gap values were estimated and compared. In pre- and postoperative audiograms, air-bone gap values at 500, 1000, 2000 and 4000 Hz frequencies were determined. Pre- and postoperative mean air-bone gap values of the patients were 23.47±4.95 and 11.58±4.77 dB, respectively. Conclusion: Our study emphasizes the fact that overall satisfactory hearing outcome with adequate air-bone closure can be achieved irrespective of cortical mastoidectomy in the surgical treatment of noncomplicated chronic ear diseases.